2016
DOI: 10.1002/2015ja022262
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the substorm current wedge by bursty bulk flows: 8 September 2002—Revisited

Abstract: The ultimate formation mechanism of the substorm current wedge (SCW) remains to date unclear. In this study, we investigate its relationship to plasma flows at substorm onset and throughout the following expansion phase. We revisit the case of 8 September 2002, which has been defined as “one of the best textbook examples of a substorm” because of its excellent coverage by both spacecraft in the magnetotail and ground‐based observatories. We found that a dense sequence of arrival of nightside flux transfer even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 65 publications
(109 reference statements)
1
12
0
Order By: Relevance
“…Thus, it is appropriate to ask the question, to what extent individual localized dipolarizations integrate into a large-scale dipolarization of the inner magnetosphere characteristic of the substorms expansion (Kepko et al, 2015)? A closely associated question, whether the so-called substorm current wedge (SCW) is composed of individual wedgelets, has received significant attention recently (Birn et al, 2011;Birn & Hesse, 2014b;Forsyth et al, 2014;Liu et al, 2015Liu et al, , 2018Malykhin et al, 2018;Palin et al, 2016;Sergeev et al, 2000). Panov et al (2016) used a fortuitous alignment of magnetospheric spacecraft and ground-based magnetometers and imagers to infer that during a weak substorm (the AE index was about 100 nT) the substorm dipolarization could have been produced by a single BBF.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is appropriate to ask the question, to what extent individual localized dipolarizations integrate into a large-scale dipolarization of the inner magnetosphere characteristic of the substorms expansion (Kepko et al, 2015)? A closely associated question, whether the so-called substorm current wedge (SCW) is composed of individual wedgelets, has received significant attention recently (Birn et al, 2011;Birn & Hesse, 2014b;Forsyth et al, 2014;Liu et al, 2015Liu et al, , 2018Malykhin et al, 2018;Palin et al, 2016;Sergeev et al, 2000). Panov et al (2016) used a fortuitous alignment of magnetospheric spacecraft and ground-based magnetometers and imagers to infer that during a weak substorm (the AE index was about 100 nT) the substorm dipolarization could have been produced by a single BBF.…”
Section: Introductionmentioning
confidence: 99%
“…Yet ground ionospheric observations have reported on multiple onsets in the course of the same substorm (Baumjohann et al, ). Further in situ observations and theoretical works have suggested that intermittent BBFs creating small “wedgelets” can be responsible for multiple onsets (e.g., Birn et al, ; Birn & Hesse, ; Liu et al, ; McPherron et al, ; Malykhin et al, ; Nakamura et al, ; Palin et al, ; Sergeev et al, ). Sparse documented proof exists on a relation between the ionospheric and plasma sheet observations, because not all BBFs can lead to global magnetotail dipolarization (Baumjohann et al, ) at GEO (Ohtani et al, ); BBFs and embedded in them DI fronts may experience tailward rebounds due to buoyancy force (Birn et al, ; Chen & Wolf, ; Nakamura et al, ; Panov et al, ; Wolf et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…All plasmasheet activation can create a SCW-like current system, as identified in ground-based magnetometer data at auroral and midlatitude regions (Palin et al, 2016;Yao et al, 2014). The standard AL index (Hsu et al, 2012) and SuperMAG electrojet indices (Gjerloev, 2009;Newell & Gjerloev, 2011) have traditionally been used to measure the substorm strength.…”
mentioning
confidence: 99%